Pemberian Hak Asuh Anak Kepada Ibu yang Murtad - Apriliani; Seno Aris Sasmito (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
This study aims to determine the maṣlaḥah of article 105 of the Compilation of Islamic Law in granting child custody to apostate mothers. This type of research includes library research namely, research that deals directly with text or data, so the typr of research used is a qualitative tipe. The conclusion is that article 105 of the Compilation of Islamic Law as the basis for granting child custody at the Surakarta Religious Courth has achieved the goal the sharia, namely creating and seeking the benefit of children in line with maṣlaḥah.